Pengaruh Pemanfaatan Aplikasi Digital Terhadap Mutu Layanan Deteksi Dini Kehamilan Resiko Tinggi - Rohmah, Siti; Susanti, Eny; Fitriah, Fitriah; Zainiyah, Zakkiyatus (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Efforts to sustainably reduce maternal mortality (MMR) through early detection of high-risk pregnancies in the Tongguh Arorbaya Primary Health Center (Puskesmas) work area are underway to support the regional MMR reduction program. The aims of this reseach were to analyze the effect of digital application utilization on the quality of high-risk pregnancy early detection services. The research method used was quasi-experimental research. The population was all public health center midwives. A sample of this research was 45 midwives. Bye using total sampling technique. Statistical analysis of this research was used the Wilcoxon signed-rank test. The results of the analysis were 0.00 of Asymp.Sig (2-tiled) which smaller than α (0.05) value, it’means indicating that the use of this digital application has a significant impact on improving the quality of early detection services for high-risk pregnancies. Therefore, it is hoped that public health center midwife’s responsibilities by continuing routine and ongoing screening to contribute to reducing MMR in Public health center work area